Analysis Of Differences In Evidence In District Court Decisions And Supreme Court Decisions: A Case Study On The Judicial Review Process - Reski Novianti; Husni Tamrin (Green Publisher Indonesia, 2024)
A judicial review (PK) is a legal mechanism given to parties who are dissatisfied with a decision that has permanent legal force, either in the District Court or the Supreme Court. In Indonesia, a PK application can only be submitted once, as regulated in Article 268 paragraph (3) of the Criminal Procedure Code, and often involves new evidence (novum) as a basis for requesting a judicial review. The objective to be achieved in this study is to analyze the differences related to the evidence in the District Court decision and the Supreme Court decision in the review process. The method used in this study is juridical normative where the legal material used covers the theory, concept, legal principles and some regulations in accordance with the discussion of research. The method of data collection used is literature study where secondary data are used such as books, laws and related journals. The results of this study indicate that the difference in evidence in conducting judicial review becomes one of the considerations for the acceptance or rejection of PK by the Supreme Court. However, in fact, the specification of the quality of evidence is still not clearly explained where it will only create a blur of norms. Therefore, it is not surprising when the Supreme Court rejected many of the judicial review considering that there was no eligibility for the quality of the evidence received